Game theory models for IEEE 802.11 DCF in wireless ad hoc networks. - Yongkang Xiao (IEEE Communications magazine)
Because wireless nodes decide their channel accesses independently in the IEEE 802.11-based ad hoc networks, and the channel access of a node has an influence on those of its neighboring nodes, game theory naturally becomes a useful and powerful tool to research this kind of network. In this article a game model is proposed to interpret the IEEE 802.11 distributed coordination function mechanism. In addition, by designing a simple Nash equilibrium backoff strategy, we present a fairness game model. Our simulation results show that the new backoff strategy can improve TCP performance almost perfectly.